Hukum Praktek Jual Beli Kotoran Hewan Menurut Mazhab Imam Syafi’i - Muhammad Shaleh; Alang Sidek; Imannullah Imannullah (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2021)
This research is included in the qualitative research model, meaning that the data used in this study is qualitative data (data that does not consist of numbers) in the form of verbal messages, dialogues and writings which are the results of research through observation, interviews and documentation. In the event of a divorce, it is the wife who suffers the most, who in particular does not have an income and a place to live. Based on the practice of the buying and selling system of animal dung in Tanjung Putus Village, Padang Tualang District, Langkat Regency, buying and selling animal dung is commonplace among the community and in accordance with sharia principles. and buying and selling rules. Starting from the pillars of buying and selling conditions, goods and so on so that the sale and purchase of animal dung in Tanjung Putus village, Padang Tualang sub-district, Langkat district according to religion can be carried out and does not violate religious norms. Based on the Islamic Shari'a Istihsan Perspective, the sale and purchase of animal dung according to unclean goods is prohibited by religion. In the development of customs that demand manure as additional fertilizer for plantations and agriculture, the sale and purchase of animal dung is legally allowed, because there are benefits. Although the Imams of Madzhab differ in their object, but with the presence of animal dung used as manure, it can be said that buying and selling transactions are allowed. Keywords: Buying and Selling, Dirt, Animals